Estudio del Mecanismo de Pirólisis de Residuos de Yuca Mediante Análisis Termogravimétrico Acoplado a la Espectroscopía Infrarroja (Revista Cientifica Ingenio Magno, 2023)
In the present work, pyrolysis of cassava residues was carried out through thermogravimetric analysis coupled with Fourier transform infrared spectroscopy (FTIR). The starting biomass residues were characterized based on calorific value. immediate and elementary analysis. The experiments were carried out using three heating rates (50, 75 and 100 K/min) in an inert atmosphere with a heating ramp from room temperature (~25 °C) to 900 °C. Initial characterization results showed that the low ash content of 1.8% by mass and the high calorific value of 15.2 MJ/kg make this residue a potential candidate for energy use. During the heat treatment in an inert atmosphere, the cassava residue experienced a main event of mass loss at 339.57 °C for 50 and 75 K/min and displacement by 34 °C when treating the sample at 100 K/min. In the thermogravimetric profiles, the samples treated at 50 and 75 K/min have similar behaviors, however, a greater loss of mass was found when the sample is submitted to 50 K/min, resulting in 12.15% of the carbonized, however at 50 K/min the decomposition rate is lower in the main event compared to the other higher heating rates. By analyzing the FTIR spectra, it was detected the formation of CO2, methane, stretching bands of the hydroxyl, methoxy and carboxyl groups attributed to alcohols, ethers and carboxylic acids, respectively, decomposition product of cellulose, hemicellulose and lignin.
Keywords: Biomass residues, cassava, TG-DTG, FTIR, pyrolysis